Photophysiology of kleptoplasts: photosynthetic use of light by chloroplasts living in animal cells - Serôdio, João
Kleptoplasty is a remarkable type of photosynthetic association, resulting from the maintenance of functional chloroplasts--the 'kleptoplasts'--in the tissues of a non-photosynthetic host. It represents a biologically unique condition for chloroplast and photosynthesis functioning, occurring in different phylogenetic lineages, namely dinoflagellates, ciliates, foraminiferans and, most interestingly, a single taxon of metazoans, the sacoglossan sea slugs. In the case of sea slugs, chloroplasts from macroalgae are often maintained as intracellular organelles in cells of these marine gastropods, structurally intact and photosynthetically competent for extended periods of time. Kleptoplasty has long attracted interest owing to the longevity of functional kleptoplasts in the absence of the original algal nucleus and the limited number of proteins encoded by the chloroplast genome. This review updates the state-of-the-art on kleptoplast photophysiology, focusing on the comparative analysis of the responses to light of the chloroplasts when in their original, macroalgal cells, and when sequestered in animal cells and functioning as kleptoplasts. It covers fundamental but ecologically relevant aspects of kleptoplast light responses, such as the occurrence of photoacclimation in hospite, operation of photoprotective processes and susceptibility to photoinhibition. Emphasis is given to host-mediated processes unique to kleptoplastic associations, reviewing current hypotheses on behavioural photoprotection and host-mediated enhancement of photosynthetic performance, and identifying current gaps in sacoglossan kleptoplast photophysiology research.